Empirical evidence for the functional benefit of intra-specific wing shape variation in a sedentary bird, the Oriental Magpie (Pica serica) - Seokbong Chae; Jusun Hwang; Jae Chun Choe; Piotr G. Jablonski; Sang-im Lee; Jooha Kim (Scientific Reports)
Abstract This study investigates the intraspecific variation in wingtip shape and its effects on aerodynamic forces and flight capabilities with the Oriental Magpies as a model species. Characterized by short and rounded wings, Oriental Magpies are highly sedentary and exhibit wingtip shape variations between juveniles and adults, as well as between males and females due to physiological changes during breeding. Analysis of 115 individuals revealed a significant interaction between sex and age in the location of the wingtip, with adult females exhibiting wings with backward-shifted wingtips than other sex and age categories. In order to examine the functional aspect of this pattern of variation, we conducted wind tunnel experiments and measured the aerodynamic performances of three wings by varying the position of wingtip from forward to backward. The results show that wings with backward-shifted wingtips have higher lift coefficient compared to wings with forward-shifted wingtips, especially at low free-stream velocities. Our findings suggest that wings with backward-shifted wingtips enhance maneuverability during both turning- and straight-flight conditions, particularly during slow gliding flight. We hypothesize that aerodynamic benefits of the backward-shifted wingtips are more important for adult females, who has increased body weight with center of mass shifted to rear part of the body due to fully developed reproductive organs including eggs and follicles. Our results suggest that age- and sex-dependent wingtip shape change can be fine-tuned according to intraspecific variation in the ecological requirements of the individuals.